2007
DOI: 10.1111/j.1745-4522.2007.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Chemical and Sensorial Profile of Extra Virgin Olive Oils Flavored With Herbs and Spices During Storage

Abstract: A study is reported on the chemical and sensorial characteristics of extra virgin olive oil flavored with hot pepper, garlic, oregano and rosemary during 7 months of storage. The oils were prepared by addition of the spice oily extracts at three different levels of concentration to an extra virgin olive oil. The following parameters were monitored: acidity, peroxide value (PV), K 232 , K 270 , (E)-2-hexenal/hexanal ratio and sensorial characteristics. At the end of the storage, all samples showed PV and K 232 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
67
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 5 publications
13
67
2
2
Order By: Relevance
“…The results are in agreement with those of Issaoui et al (2011) who reported that lemon and thyme at high concentrations (80 g/kg of oil) weren't efficient to protect the olive oils from thermo-oxidative processes. Moreover, pro-oxidant action of product used at high concentrations to enrich olive oil, was also previously reported by Sousa et al (2015) and Gambacorta et al (2007).…”
Section: Accelerated Oxidation Of Oil By Oven-testsupporting
confidence: 73%
See 1 more Smart Citation
“…The results are in agreement with those of Issaoui et al (2011) who reported that lemon and thyme at high concentrations (80 g/kg of oil) weren't efficient to protect the olive oils from thermo-oxidative processes. Moreover, pro-oxidant action of product used at high concentrations to enrich olive oil, was also previously reported by Sousa et al (2015) and Gambacorta et al (2007).…”
Section: Accelerated Oxidation Of Oil By Oven-testsupporting
confidence: 73%
“…The flavouring of oil is one of the parts of this process of diversification. Therefore, various studies have previously shown the beneficial effects of the addition of aromatic plants (thyme, rosemary, lavender, basil) (Ayadi et al 2009), herbs and spices (Gambacorta et al 2007) on the stability and sensorial characteristics of olive oil. MoldaoMartins et al (2004) have studied the effect of essential oils extracted from Mentha 9 Pipertia and Thymus mastichia L. on the quality of olive oil.…”
Section: Introductionmentioning
confidence: 99%
“…By studying quality indices during storage of flavoured olive oils, Baiano, Terracone, Gambacorta, and La Notte (2009) observed that those with garlic retained their indices below the maximum allowed for extra-virgin olive oils. Gambacorta et al (2007) reported that the addition of different concentrations of garlic, hot pepper, oregano, and rosemary at long term improved the stability of the olive oils. Some works studied the changes in the oxidative status of flavoured olive oils to verify the efficiency of flavourings bioactive properties and their contribution to olive oils stability.…”
Section: Introductionmentioning
confidence: 98%
“…Only a few studies report the extraction of antioxidant compounds from herbs [10]. In this context, some flavored olive oils have been prepared and different quality parameters are described in the literature [12,13].…”
Section: Introductionmentioning
confidence: 99%